2020
DOI: 10.1016/j.ajpath.2020.07.012
|View full text |Cite|
|
Sign up to set email alerts
|

Medical Treatment Can Unintentionally Alter the Regulatory T-Cell Compartment in Patients with Widespread Pathophysiologic Conditions

Abstract: Regulatory T cells (Tregs) are non-redundant mediators of immune tolerance that are critical to prevent autoimmune disease and promote an anti-inflammatory tissue environment. Many individuals experience chronic diseases and physiologic changes associated with aging requiring long-term medication. Unfortunately, adverse effects accompany every pharmacologic intervention and may affect overall outcomes. We focus on medications typically prescribed during the treatment of prevalent chronic diseases and disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 138 publications
(163 reference statements)
0
3
0
Order By: Relevance
“…The regulatory function of metformin on Tregs has not yet been clarified in obese asthma. In some immune-related inflammatory diseases, metformin inhibits the formation of the germ centre of the spleen and up-regulates Tregs to inhibit the formation of Teff cells, inhibiting the production of autoantibodies15 to exert an anti-inflammatory and anti-autoimmune role. Hence, it is vital and necessary to explore the mechanism by which metformin plays an anti-inflammatory role by increasing the Tregs in obese asthma.In summary, we found that (a) obese asthmatic mice showedmore severe airway inflammation; (b) metformin alleviated airway inflammation and increased Tregs in obese asthma.…”
mentioning
confidence: 99%
“…The regulatory function of metformin on Tregs has not yet been clarified in obese asthma. In some immune-related inflammatory diseases, metformin inhibits the formation of the germ centre of the spleen and up-regulates Tregs to inhibit the formation of Teff cells, inhibiting the production of autoantibodies15 to exert an anti-inflammatory and anti-autoimmune role. Hence, it is vital and necessary to explore the mechanism by which metformin plays an anti-inflammatory role by increasing the Tregs in obese asthma.In summary, we found that (a) obese asthmatic mice showedmore severe airway inflammation; (b) metformin alleviated airway inflammation and increased Tregs in obese asthma.…”
mentioning
confidence: 99%
“…Примечательно, что ряд плейотропных биологически активных веществ, уже применяемых для лечения ишемического инсульта, также влияют и на Treg [96]. Например, к модуляторам Treg относятся мелатонин, эстроген, статины, витамин D и др.…”
Section: подходы к модуляции уровня Treg для терапии ишемического инс...unclassified
“…Например, к модуляторам Treg относятся мелатонин, эстроген, статины, витамин D и др. [96]. Мелатонин привлекателен тем, что он давно известен в качестве нейропротектора, в том числе при лечении цереброваскулярной патологии [97].…”
Section: подходы к модуляции уровня Treg для терапии ишемического инс...unclassified
“…IL-6 blockade is not the only approach with indirect Treg-boosting effects. Others tested for such purpose include mTOR inhibitors (rapamycin, metformin), low-dose IL-2, TNFR2 agonists, rituximab, vitamin D, and others ( Copsel et al., 2020 ; Eggenhuizen et al., 2020 ; Fisher et al., 2019 ; Göschl et al., 2019 ; Rosenzwajg et al., 2019 ; Sharabi et al., 2018 ). Flow-cytometry, CyTOF and co-culture assays of Tregs during clinical trials could advance knowledge on novel mechanisms in psychosis, which we discuss in topic 4.…”
Section: Tregs: Role In the Neuroimmune Network And Therapeutic Implicationsmentioning
confidence: 99%